IMMU-29. B-CELL-BASED VACCINE PRODUCES GLIOBLASTOMA-REACTIVE ANTIBODIES THAT CONTRIBUTE TO TUMOR CLEARANCE. (12th November 2021) - Castro, Brandyn; Dapash, Mark; Hou, David; Rashidi, Aida; Kanojia, Deepak; Zhang, Peng; Lopez-Rosas, Aurora; Han, Yu; Balyasnikova, Irina; Stupp, Roger; Miska, Jason; Lesniak, Maciej; et al.
Abstract: Glioblastomas (GBM) are characterized by a strong immunosuppressive environment, contributing to their poor prognosis and limited therapeutic response to immunotherapies. B-cells represent a unique opportunity to promote immunotherapy due to their potential to kill tumors by both cellular and humoral immunity. To generate our B-cell-based vaccine (BVax ) platform, we activated 41BBL + B cells from tumor bearing mice or GBM patient blood with BAFF, CD40, and IFNg. We have previously demonstrated that BVax potentiates radiation therapy, temozolomide and checkpoint blockade in murine models of GBM via enhancement of CD8 + T-cell based immunity. The aim of this current study is to evaluate the humoral effector functions of BVax . We examined the antibody (Ab) repertoire in vivo from serum of tumor-bearing B-cell knockout mice treated with BVax or by ex vivo stimulation of patient-derived BVax . Upon systemic administration, BVax infiltrates the tumor where it differentiates into plasmablasts. Murine BVax - and BNaive -derived serum immunoglobulin generated in vivo showed that the majority of murine BVax -derived Ab were IgG isotype, while BNaive mainly produced IgM isotype. Transfer of IgG from BVax treated mice directly into tumors of recipient animals significantly prolonged their survival, demonstrating anti-tumor cytotoxicity directly through humoral immunity. Patient-derived BVax activated ex vivo showed a plasmablast phenotype and the Ab repertoire supports the previous findings seen in our murine model. Our work suggests BVax -derived IgGs role in antibody-dependent cellular cytotoxicity and improved survival in murine models. This function, in addition to its role in cellular immunity against GBM, renders BVax a potentially effective alternative immunotherapeutic option for GBM patients.